The Financial Impact of the Proposed Amendments to IAS 17: Evidence from Belgium and the Netherlands - Deborah Branswijck; Stefanie Longueville; Patricia Everaert (Journal of Accounting and Management Information Systems (JAMIS), 2011)
Prior literature examined the financial impact of capitalizing operating leases by using the constructive lease capitalization method of Imhoff et al. (1991). The empirical evidence of these studies results in the perception that operating leases lead to off-balance financing, improvements of financial ratios and earnings enhancement in the U.K. (e.g. Beattie et al., 1998) and in the U.S.(e.g. Ely, 1995). Therefore, the IASB published in 2010 the exposure draft for the new standard on lease accounting (IAS 17). The most striking change is the elimination of the difference between finance and operating lease. Our study investigates the impact of the proposed adaptation for listed companies in Belgium and the Netherlands for 2008. Our results indicate that debt to equity ratio, return on assets and the current ratio are significantly affected by capitalizing operating leases. Furthermore, the results show that the impact on financial ratios differs among industries.
Keywords: M41; 650; International accounting; lease accounting; lease capitalization; financial ratios; listed firms